3D Process-Oriented Gravity Modelling applied north of 49°S on the Argentine continental margin. (January 2018) - Pedraza De Marchi, Ana C.; Ghidella, Marta E.; Tocho, Claudia N.
Abstract: The Process-Oriented Gravity Modelling (POGM) technique represents a useful way to distinguish the contribution that different geological processes make to the observed gravity in passive margins. The POGM is an innovative gravity modelling approach that can give us information about the role that processes such as sedimentation and magmatic underplating, together with their loading effects, may play in the evolution of a margin. In this work, the POGM methodology has been applied with in a 2D and 3D approach. 2D profiles spaced every one arc-minute in the area of the Argentine continental margin, between 38.5°S and 49°S latitude and 64°W and 50°W longitude, were used to generate the latter. The 3D POGM was also solved and the result was compared with that obtained from 2D profiles. The comparison with the observed anomaly, using the 3D approach from 2D profiles gave results with enhanced resolution. The best fit between the calculated and observed gravity anomaly is given by an effective elastic thickness of 15 km. A cortical thickness map obtained as a result of the POGM calculations shows basin areas characterized by a thinned crust and a structural variation where the continental-oceanic boundary (COB) could be indicated. Besides, results of POGM allow us to detect an alignment between the Valdés and Rawson basins and possibly a third basin as a probable aulacogen. A stretching factor analysis shows that in these basins a stretching period existed but it did not reach the stage of oceanic crust formation. A strong positive residue in the Colorado basin is shown by the flexural isostatic anomaly, suggesting that the basin may continue in subsidence. Highlights: The Process-Oriented Gravity Modelling (POGM) was applied for the first time on the Argentine continental margin. A laborious attempt, 3D POGM from 2D POGM, to improve the resolution of the innovative gravity anomalies disjointed by POGM was explored. The continental-oceanic boundary (COB) could be indicated by a strong gradient of the crustal thickness. An alignment between the Valdés and Rawson basins and possibly a third basin was pointed out as a probable aulacogen. A strong positive residue in the Colorado basin suggests that the basin may continue in subsidence. The characterization of the Argentine margin area with the best fit T e = 15 km is a first approximationto solve the complex margin structure.